Implementation of a telehealth videoconference to improve hospital‐to‐skilled nursing care transitions: Preliminary data. Issue 6 (25th March 2022) - Bellantoni, Julia; Clark, Elspeth; Wilson, Jonathan; Pendergast, Jane; Pavon, Juliessa M.; White, Heidi K.; Malone, Deanna; Knechtle, William; Jolly Graham, Aubrey
Abstract: Background: Transition‐related patient safety errors are high among patients discharged from hospitals to skilled nursing facilities (SNFs), and interventions are needed to improve communication between hospitals and SNF providers. Our objective was to describe the implementation of a pilot telehealth videoconference program modeled after Extension for Community Health Outcomes‐Care Transitions and examine patient safety errors and readmissions. Methods: A multidisciplinary telehealth videoconference program was implemented at two academic hospitals for patients discharged to participating SNFs. Process measures, patient safety errors, and hospital readmissions were evaluated retrospectively for patients discussed at weekly conferences between July 2019–January 2020. Results were mapped to the constructs of the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE‐AIM) model. Descriptive statistics were reported for the conference process measures, patient and index hospitalization characteristics, and patient safety errors. The primary clinical outcome was all‐cause 30‐day readmissions. An intention‐to‐treat (ITT) analysis was conducted using logistic regression models fit to compare the probability of 30‐day hospital readmission in patients discharged to participating SNFs across 7 months prior to after telehealth project implementation. Results: There were 263 patients ( 67% of eligible patients) discussed during 26 telehealth videoconferences. Mean discussion time per patient was 7.7 min and median prep time per patient was 24.2 min for the hospital pharmacist and 10.3 min for the hospital clinician. A total of 327 patient safety errors were uncovered, mostly related to communication (54%) and medications (43%). Differences in slopes (program period vs. pre‐implementation) of the probability of readmission across the two time periods were not statistically significant (OR 0.95, [95% CI 0.75, 1.19]). Conclusions: A pilot care innovations telehealth videoconference between hospital‐based and SNF provider teams was successfully implemented within a large health system and enhanced care transitions by optimizing error‐prone transitions. Future work is needed to understand process flow within nursing homes and its impact on clinical outcomes.